IMPLEMENTATION OF INNOVATION AND DIGITAL TECHNOLOGIES IN THE INFORMATION EDUCATION ENVIRONMENT - Manzura Ibragimovna Azizova (Galaxy International Interdisciplinary Research Journal, 2022)
Digital economy is a system of implementation of economic, social and cultural relations based on the use of digital technologies. It can sometimes be referred to as the internet economy, the new economy, or the web economy.